2000
DOI: 10.1034/j.1600-0676.2000.020003253.x
|View full text |Cite
|
Sign up to set email alerts
|

Do gastric and oesophageal varices bleed at different portal pressures and is TIPS an effective treatment?

Abstract: In this study, there was no difference between the pressures at which gastric and oesophageal varices bled. Rebleeding and mortality rates were similar in the two groups. TIPS is equally effective in the treatment of both oesophageal and gastric variceal haemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…Chau et al also found that portal pressure in patients who had early rebleeding before seven days was lower in patients with GVB. 26 Rees and colleagues 27 did not demonstrate significant differences in PPG prior to TIPSS which was >20 mm Hg in both groups. This study was limited by a small number of patients and a short follow up period.…”
Section: Discussionmentioning
confidence: 99%
“…Chau et al also found that portal pressure in patients who had early rebleeding before seven days was lower in patients with GVB. 26 Rees and colleagues 27 did not demonstrate significant differences in PPG prior to TIPSS which was >20 mm Hg in both groups. This study was limited by a small number of patients and a short follow up period.…”
Section: Discussionmentioning
confidence: 99%
“…In some series, the initial HVPG in patients with gastric varices was lower than that of patients with esophageal varices, whereas in other series no differences were observed. [81][82][83] In these small series, TIPS was equally effective at controlling bleeding from gastric as well as esophageal varices. [81][82][83][84] Controlled trials comparing surgical shunts or glue in the treatment of these patients would help to better define the role of TIPS in the management of patients with bleeding from gastric varices.…”
Section: Bleeding From Gastric Varicesmentioning
confidence: 99%
“…[81][82][83] In these small series, TIPS was equally effective at controlling bleeding from gastric as well as esophageal varices. [81][82][83][84] Controlled trials comparing surgical shunts or glue in the treatment of these patients would help to better define the role of TIPS in the management of patients with bleeding from gastric varices. In the authors' opinion, TIPS is an important tool in the control of gastric variceal bleeding, though the final portosystemic gradient required to achieve variceal decompression may be lower than what is required for esophageal variceal bleeding, and embolization of the varices also may be required.…”
Section: Bleeding From Gastric Varicesmentioning
confidence: 99%
“…The advantage of stent-grafts in TIPS is its ability to separate the shunt channel from the liver parenchyma, bile ducts, and the wall of the hepatic vein, preventing development of pseudointimal and intimal hyperplasia [2,4,11]. The stentgraft has also been used to treat hemorrhage after extrahepatic portal vein puncture during a TIPS procedure [16].…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological examination from the affected liver segment showed no divergent pattern. Stentgrafts used in TIPS block the outflow from the liver vein, but do not have a prolonged circulatory effect and do not affect the liver parenchyma.Key words: Portal hypertension-Transjugular intrahepatic portosystemic shunt-Stent-graft-Hepatic vein occlusion Over the last 10 years, transjugular intrahepatic portosystematic shunt (TIPS) procedures have almost completely replaced surgical portosystemic shunts in treatment of patients with portal hypertension and repeated bleeding from gastroesophageal varices [1][2][3][4][5] or refractory ascites. Longterm results of TIPS are, however, unsatisfactory due to the development of pseudointimal hyperplasia in the shunt channel and/or intimal hyperplasia in the adjacent hepatic vein [6].…”
mentioning
confidence: 99%